Estudo da remoção de cor de efluente têxtil por eletrocoagulação - Pessoa, Germana de Paiva (2008)
The textile effluent color resultant from dyes polymeric structures is a problem for textile industries. Amongst the treatment techniques for this type of effluent, it is emphasized the electrocoagulation (EC), which consists of a physicochemical technique applied for either color or organic pollutants removal. In this work, three stages of the EC process, in batch, for dye color removal were assessed. In the first stage (synthetic effluent and primary aluminum electrodes), the reactive dye Remazol Blue RR was used and the effect of operational parameters such as electric current density, initial solution pH, electrolysis time, initial dye concentration, solution conductivity, chemical oxygen demand (COD) and the energy consumption was verified, reaching a color removal of 98% and 100%, for the treatment time of 20 and 40 minutes, respectively. In the optimized operational conditions, 98% of color removal and 97 % of DQO removal were obtained, resulting a process cost of R$ 2,62 per m3 of treated effluent. In the second stage (synthetic effluent and electrodes made from cans), a color removal of 90% and 95%, for the treatment time of 20 and 30 minutes, was verified, respectively. It is important to mention that, for the time of 20 minutes, the operational cost was R$ 0,95, whereas, for 30 minutes, was R$ 1,42 per m3 of treated effluent. In the third stage, real textile effluent from Benatêxtil, a textile industry located in Fortaleza city – Ceará, and primary aluminum electrodes were used. The best result for color removal was 77,63%, with dilution of 5%, treatment time of 30 minutes and initial pH 3,0. The calculated energy cost for this stage was of R$ 2,01 per m3 of treated effluent. In this study it was possible to verify that the electrocoagulation process can be efficient in the color removal of a synthetic textile effluent composed of dyes, but, for the real textile effluent without a previous treatment, it is necessary to dilute it due to its high dye concentration and conductivity.